Peningkatan Brand Awareness Melalui Konten Video TikTokMenggunakan Aplikasi CapCut Pro pada UMKM Larina Hijab - Lintang Permata; Heru Utomo; Rr. Tri Istining Wardani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
TikTok has become an effective digital marketing platform for Micro, Small, and Medium Enterprises (MSMEs), including Larina Hijab, a Muslim fashion MSME in Pasuruan Regency. Its TikTok content had remained monotonous and provided limited product information, resulting in suboptimal brand awareness. This study aims to analyze the effect of TikTok video content on improving brand awareness and to examine the use of the CapCut Pro application in producing quality video content. This research used the action research method with a quantitative descriptive approach, covering four stages: planning, action, observation, and reflection. Data were collected through interviews, observation, documentation, and questionnaires involving 24 respondents, consisting of the owner, an employee, digital marketing experts, and consumers. TikTok Analytics data were analyzed descriptively, while video quality was analyzed using a 5-point Likert scale based on grammar of edit indicators. After five videos were uploaded, the TikTok account gained a 13.4% increase in followers, 172% in views, 252.8% in profile visits, 423.1% in likes, and 106.3% in shares, with 67.3% of traffic from the For You Page and 91% of viewers being non-followers. All grammar of edit indicators scored above 75%, categorized as very good, with sound design highest (90.4%) and color grading lowest (83.3%). The findings show that TikTok video content edited with CapCut Pro effectively improves brand awareness and produces quality content without requiring complex editing skills.